2009
DOI: 10.1152/ajpendo.00245.2009
|View full text |Cite
|
Sign up to set email alerts
|

Motor unit number estimate as a predictor of motor dysfunction in an animal model of type 1 diabetes

Abstract: is a common complication of diabetes that leads to severe morbidity. In this study, we investigated the sensitivity of motor unit number estimate (MUNE) to detect early motor axon dysfunction in streptozotocin (STZ)-treated mice. We compared the findings with in vitro changes in the morphology and electrophysiology of the neuromuscular junction. Adult Thy1-YFP and Swiss Webster mice were made diabetic following three interdaily intraperitoneal STZ injections. Splay testing and rotarod performance assessed moto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 49 publications
1
31
1
Order By: Relevance
“…The velocity at which mice fell from the rod when the speed was increased by 4 rpm every 40 s was equivalent to control for mice at 2 and 4 wk after the onset of STZ-induced hyperglycemia. However, maximal neurally evoked twitch tension of the EDL muscle declined significantly to 1,514 Ϯ 23.16 g from the control value of 1,711 Ϯ 24.5 g at the 4-wk time point (Fig. 1B) when MUNE also had declined to 187.2 Ϯ 10.6 from the control value of 298.9 Ϯ 8.55 (67).…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations
“…The velocity at which mice fell from the rod when the speed was increased by 4 rpm every 40 s was equivalent to control for mice at 2 and 4 wk after the onset of STZ-induced hyperglycemia. However, maximal neurally evoked twitch tension of the EDL muscle declined significantly to 1,514 Ϯ 23.16 g from the control value of 1,711 Ϯ 24.5 g at the 4-wk time point (Fig. 1B) when MUNE also had declined to 187.2 Ϯ 10.6 from the control value of 298.9 Ϯ 8.55 (67).…”
Section: Resultsmentioning
confidence: 87%
“…Specifically, AChE activity and mRNA levels of rat fast muscle are reduced after denervation, paralysis, or alteration of activity patterns (13,32,66). Although we did not specifically evaluate the EDL activity, an earlier study demonstrated that hindlimb compound muscle action potential amplitude values and motor strength were relatively spared in 4-wk diabetic mice (67). Furthermore, we failed to detect expression or function of embryonic AChRs in muscles with diabetes-induced reduction of AChE.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Evidences that DPN causes a loss of MUs have previously been described (Souayah et al, 2009;Allen et al, 2013;Allen et al, 2014a) and could indeed be contributing to the augmented force variability. Dideriksen et al (2012) also suggest that decreases in the force steadiness might be related to reductions in the size of MU populations.…”
Section: Amount Of Force Variabilitymentioning
confidence: 73%